The Economic Performance and Size of Firms: the Case of Russian Health Resort Market - Pakhomova, Nadezda Victorovna; Kazmin, Alexey Anatolyevich; Kvadritsius, Natalia Viktorovna (Economy of Regions, 2017)
The article shows how external and internal macro-economic factors (the reduction of real income of the population, the depreciation of the local currency to the US dollar in 2014 -2015, the promotion of Crimea as a direction for health and resort services for Russian citizens) impact on the financial and economic indicators of health and resort organizations in Russia during 2012-2015. The calculations based on a variety of Federal Service of State Statistics data demonstrate the positive dynamics of the development of regional markets of health and resort services, due to the regional markets of health and resort services of Krasnodar, Stavropol and Altai regions and due to the inclusion of the Federal District of Crimea within the Russian macroeconomic indicators. The econometric model based on a sample of 272 organizations proves the hypothesis about the more beneficial impact of the changes in macroeconomic factors for large health and resort organizations (with a total annual revenue of 400 million roubles) compared with smaller organizations. It is expressed in the growth of sales profitability and annual revenue. The calculations have shown that the organization size as an independent variable in a sample of data related to 2014-2015, increased its positive influence on the dependent variable of annual revenue growth comparing to sampling for 2012-2013. The tough financial constraints in the country trigger the discussion of new opportunities and tools for the development of market conditions, which will stimulate the demand for investment in material and technical base renewal and innovations from the side of large health and resort organizations. In addition to improving the transport accessibility of federal resort regions and measures for promoting and improving the quality of the general health and resort infrastructure, there are discussions to create a favorable competitive environment, improve the public procurement system (including the procurement of state-owned companies), as well as to stimulate the market participants to introduce product, marketing and organizational innovations.